2023
DOI: 10.1021/acsapm.3c02003
|View full text |Cite
|
Sign up to set email alerts
|

High Thermally Stable Anthracene-Based Polyimides with Low Dielectric Constants and Dissipation Factors

Yueh-Hsing Lee,
Jin-Wei Lin,
Yu-Chen Huang
et al.

Abstract: At present, high-performance polymers with low dielectric constants (D k ) and low dissipation factors (D f ) have gained much attention with the rapid evolution of microelectronic and 5G communication technologies. Due to their excellent thermal stabilities, heat resistances, mechanical strengths, and dielectric properties, polyimides (PIs) have attracted a lot of attention. Herein, a series of anthracene (An)-based PIs are synthesized from an ester-functionalized anthracene diamine (An-NH 2 ) monomer and fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…5D illustrates the dielectric constant and dielectric loss values for several common materials. 43–48 Among them, CP-93 prepared in this study, showed the lowest dielectric constant and dielectric loss values. In addition, the lower raw material cost of P(MP- co -DSH)s and the low density (0.835) of PMP polymers effectively reduce material cost.…”
Section: Resultsmentioning
confidence: 77%
“…5D illustrates the dielectric constant and dielectric loss values for several common materials. 43–48 Among them, CP-93 prepared in this study, showed the lowest dielectric constant and dielectric loss values. In addition, the lower raw material cost of P(MP- co -DSH)s and the low density (0.835) of PMP polymers effectively reduce material cost.…”
Section: Resultsmentioning
confidence: 77%
“…We believe that this polymer cross-linker should have excellent properties and thus become a good auxiliary material for EA resins. In recent reports, polyimides are known for their excellent thermal stability, , good mechanical properties, and chemical resistance, , and polyimides are highly designable in terms of their functionality. Among them, photosensitive polyimides can be cured under UV-light, , and the modification of EA resins with photosensitive polyimides is a valid method to improve the mechanical and thermomechanical properties of resins.…”
Section: Introductionmentioning
confidence: 99%